(untitled) (Global Journal of Management and Business Research, 2015)
The investors tend to investing in companies which have low risk and high expected efficiency and upstream shares price turbulence and in this regard the operational risk is a factor which results in the decrease of above criteria and confronts the company with the risk of bankruptcy, hence the investors have less motive for investing and the company has no choice but to use the financial leverages optimally in order to provide financially and in this situation the company’s shares price is without fluctuation and stays in the lowest price. In this study the researcher has used the correlation approach-post events in the range of 1388 -1392 -to investigate the effects of operational risk (bankruptcy risk) on the turbulence of shares price, the expected efficiency of the shares and since the operational risk variable is not normally distributed, the data attribute is changed from gradation to order and finally the Logistic Regression Test is used for testing the hypotheses of the research.